Ottoman Mosques In Sana'a, Yemen Archeological And Architectural Study - Rahman, Mohamed Ahmed Abd El (Journal of Islamic Architecture, 2017)
The Ottoman presence in Yemen is divided into two periods, first period from 945 AH until 1045 AH, and then the second from 1289 AH until 1336 AH, Ottomans interested during their presence in Yemen to establish different types of charitable buildings especially, religious buildings, which include mosques, madrassas, and shrines. The aim of interest of Ottomans governors to make significant civilized and architectural renaissance in Yemen, especially Sana'a, with emphasis on establishment mosques to get closer to God and to gain sympathy and love of the people of Yemen. Most of these mosques do the role of the madrassas as documents indicate like mosque of Özdemir, Al-Muradiyya and Al-Bakiriyya therefore, Ottomans are Hanifite Sunni and want by these mosques to facing shite and spread Sunni.In this paper researcher will discuss styles of Ottoman mosques in Sana'a. There are eight mosques, seven dates to the first period of Ottomans in Yemen and only one date to the second period of Ottomans in Yemen.